A audiência preliminar como interregno procedimental : uma contribuição para o processo penal brasileiro - Sant'Anna, Marcelo Almeida (2018)
Doctorate thesis in Criminal Sciences, developed in Concentration Area Criminal System and Violence and linked in Field of Research Contemporary Legal-Criminal Systems. The analysis of the criminal field allows us to evidence the existence of a constitutional deficit, especially in the preliminary phase of the criminal process. Investigation, as a space of power and as a procedure for the production of truths, is not properly connected to the procedural stage, which ends up by broadening excessively discretion, producing unilateral knowledge. Adversary proceeding and right to a fair hearing are constitutional principles applicable to both stages of criminal prosecution, albeit at different intensity. Therefore, there is a need for a procedural interim period prior to the criminal complaint, made in the form of a preliminary hearing. In the end, the a result of reaserch allowed device a bill.